Performance, profitability and greenhouse gas emissions of alternative finishing strategies for Holstein-Friesian bulls and steers. (6th February 2018) - Murphy, B.; Crosson, P.; Kelly, A. K.; Prendiville, R.
Abstract : Modifying finishing strategies within established production systems has the potential to increase beef output and farm profit while reducing greenhouse gas (GHG) emissions. Thus, the objectives of this study were to investigate the effects of finishing duration on animal performance of Holstein-Friesian (HF) bulls and steers and evaluate the profitability and GHG emissions of these finishing strategies. A total of 90 HF calves were assigned to a complete randomised block design; three bull and three steer finishing strategies. Calves were rotationally grazed in a paddock system for the first season at pasture, housed and offered grass silage ad libitum plus 1.5 kg DM of concentrate per head daily for the first winter and returned to pasture for a second season. Bulls were slaughtered at 19 months of age and either finished indoors on concentrates ad libitum for 100 days (19AL), finished at pasture supplemented with 5 kg DM of concentrate per head daily for 100 (19SP) or 150 days (19LP). Steers were slaughtered at 21 months of age and finished at pasture, supplemented with 5 kg DM of concentrate per head daily for 60 (21SP) and 110 days (21LP) or slaughtered at 24 months of age and finished indoors over the second winter on grass silage ad libitum plus 5 kg DM of concentrate per head daily (24MO). The Grange Dairy Beef Systems Model and the Beef Systems Greenhouse Gas Emissions Model were used to evaluate profitability and GHG emissions, respectively. Average daily gain during the finishing period ( P <0.001), live weight at slaughter ( P <0.01), carcass weight ( P <0.05) and fat score ( P <0.001) were greater for 19AL than 19SP and 19LP, respectively. Similarly, concentrate dry matter intake was greater for 19AL than 19SP; 19LP was intermediate ( P <0.001). Live weight at slaughter ( P <0.001), carcass weight ( P <0.001), conformation score ( P <0.05) and fat score ( P <0.001) were greater for 24MO than 21SP and 21LP, respectively. During the finishing period concentrate dry matter intake was greater for 21LP than 21SP with 24MO intermediate; 542, 283 and 436 kg DM, respectively. Although pasture-based finishing strategies had lower gross output values, concentrate feed costs were also reduced thus net margin was greater than indoor finishing strategies. Reducing concentrate input increased GHG emissions for bulls and steers slaughtered at the same age, respectively. Although prolonging the finishing duration reduced GHG emissions for bull and steer production systems, finishing bulls and steers over a longer period at pasture did not enhance animal performance and profit.